Grasses of Sardhana - Singh, Udai; Singh, V. (Indian Forester, 1968)
In this paper the authors have enumerated 48 genera and 59 species of grasses from Sardhana Tehsil in Meerut district. Of these 24 genera and 33 species belong to the subfamily Panicoideae and 19 genera and 26 species to the subfamily Pooideae. The tribes Paniceae and Andropogoneae have the largest number of species, i.e., 17 and 15 respectively.